A Study Of Maternal And Fetal Outcomes In Gestational Diabetes Mellitus - Maddala Hima Varsha; K Vandana; Munni SK (International Journal of Health and Clinical Research, 2022)
Aim: To study maternal and fetal outcomes in patients with gestational diabetes mellitus Objectives: To study the maternal outcome in terms of mode of delivery, antepartum, Intrapartum and post -partum complications To study fetal outcome in terms of maturity, birth weight, presence of congenital anomalies, and neonatal complications in cases of gestational diabetes. Materials and Methods: In this prospective observational study we included 30 patients with gestational diabetes mellitus and were studied for feto-maternal outcome. Results: In this present study 30 cases of gestational diabetes mellitus were studied. It was observed that gestational diabetes mellitus maximum among patients belonged to age group 26-30 years (33%), maximum seen among multigravida patients (56%). 50% cases delivered by caesarean section, maternal complications like preeclampsia (8 cases), polyhydramnios (13 cases), uteroplacental insufficiency (3 cases), macrosomia (5 cases), intrauterine fetal death (1 case). 6 neonates developed respiratory distress syndrome, 10 developed hypoglycemia, and 11 neonates required NICU admission. Conclusion: Gestational diabetes mellitus poses short term as well as long term effects on the health of both mother and the child. Therefore all antenatal women attending the OPD should be offered universal screening for GDM. Early diagnosis and treatment of gestational diabetes with adequate antenatal care, timely referral, management of the identified cases are essential to reduce the adverse maternal and neonatal outcomes.